Analysis Of Illocutionary Speech Acts In The Text Of The Inaugural Speech Of A Prophet, Faculty Of Engineering, Tarumanagara University By Tri Harso Karyono - Salsabila Budi Utami; Luthfita Dina Alawiyah; Adennia Thaffana; Ariandhani Rari; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Nurnaningsih Nurnaningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to examine illocutionary speech acts in the text of the speech